Maps to accompany annual report of the Departament of Mines New South Wales for the year 1879 - Government Printing House (Sydney); Department of Mines (Sydney) (Thomas Richards, 1880)
Pittman Edward F.: Notes to accompany geological map of Hill-End and Tambaroora - s. 3, 1 nlb.
Department of Mines. Sydney ; Thomas Richards ; drawn and etched in the Compiling Branch by H. A. James ; geologically and topographically surveyed by Edward F. Pittman [...] ; W.S. Campbell chief Draftsman ; Parrot L. S.
Keywords: Mapy geologiczne; Kartografia; Nowa Południowa Walia (Australia); w kartografii